2021
DOI: 10.1016/j.jdin.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis in adults: A cross-sectional study in the department of dermatology, Antananarivo, Madagascar

Abstract: Background: Although atopic dermatitis (AD) is becoming a pressing public health concern in the world, Madagascar is underrepresented in the AD literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…The subjects in this study were dominated by females, as many as 75.56%. This is in accordance with previous epidemiological studies which said that atopic dermatitis was more common in female than male with a ratio of 1.27-2 : 1.1 (Munthaha et al, 2021;Sendrasoa et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The subjects in this study were dominated by females, as many as 75.56%. This is in accordance with previous epidemiological studies which said that atopic dermatitis was more common in female than male with a ratio of 1.27-2 : 1.1 (Munthaha et al, 2021;Sendrasoa et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the theory which stated that AD usually coexists with other atopic disorders such as allergic rhinitis, asthma, and food allergy (Solomon et al, 2019). This is also consistent with a prior study that found that 70% of AD patients had a first-degree relative who had atopy (Sendrasoa et al, 2021). The sensitization to HDM detected with local SPT was found in 26 subjects (57.77%).…”
Section: Discussionsupporting
confidence: 92%
“…Low education level as a factor of poor treatment adherence in our study is consistent with the factors influencing therapeutic adherence according to the WHO [7]. Factors associated with high adherence include patient-related factors such as health literacy.…”
Section: Study Resultssupporting
confidence: 86%
“…The prevalence of Ad continues to increase both in children and in adults in Madagascar. 39 Most AD patients are seen by general practitioners or by paediatricians before visiting dermatologists. So, most of cases seen by dermatologists are moderate to severe.…”
Section: Madagascarmentioning
confidence: 99%